Inclusive Comedy and Disability Representation in Clash of Mutants - Harnina Ridwan; Fera Tri Susilawaty (Ikatan Sarjana Komunikasi Indonesia, 2026)
This study is a qualitative case study examining the representation of disability in digital media, focusing on the inaugural episode of Clash of Mutants on YouTube. Grounded in Communication Studies and Representation Theory, as well as the social model of disability, this study analyzes how meaning is constructed through dark comedy. It hypothesizes that the use of the label mutants within dark comedy creates ambivalent meanings, simultaneously enabling inclusive representation while reinforcing stigma. This research applies a qualitative case study design. The data consist of one episode analyzed through qualitative content analysis of visual and narrative elements, supported by 100 audience comments explored using sentiment analysis. The main outcomes include forms of representation, narrative framing, and audience reception toward inclusive representation in digital communication. The findings reveal ambivalence: persons with disabilities are presented as active subjects in digital entertainment yet framed through stereotypes of incapacity. The contrast between formal competition aesthetics and disabled bodies opens space for inclusive representation while reproducing stigma through dark comedy. Audience reception is dominated by hegemonic-dominant readings, with viewers emphasizing entertainment over critical reflection, thereby normalizing the mutants label. These findings align with prior studies on humor’s dual role as critique and marginalization. In conclusion, this case study highlights the complexity of dark comedy in shaping inclusive representation. Theoretically, it integrates representation, humor, and reception studies; practically, it informs more ethical and participatory content strategies.